Rituximab in Membranous Nephropathy - Gauckler, Philipp; Shin, Jae Il; Alberici, Federico; Audard, Vincent; Bruchfeld, Annette; Busch, Martin; Cheung, Chee Kay; Crnogorac, Matija; Delbarba, Elisa; Eller, Kathrin; Faguer, Stanislas; Galesic, Kresimir; et al. (Kidney international reports, 2021)
Membranous nephropathy (MN) is the most common cause of primary nephrotic syndrome among adults. The identification of phospholipase A2 receptor (PLA2R) as target antigen in most patients changed the management of MN dramatically, and provided a rationale for B-cell depleting agents such as rituximab. The efficacy of rituximab in inducing remission has been investigated in several studies, including 3 randomized controlled trials, in which complete and partial remission of proteinuria was achieved in approximately two-thirds of treated patients. Due to its favorable safety profile, rituximab is now considered a first-line treatment option for MN, especially in patients at moderate and high risk of deterioration in kidney function. However, questions remain about how to best use rituximab, including the optimal dosing regimen, a potential need for maintenance therapy, and assessment of long-term safety and efficacy outcomes. In this review, we provide an overview of the current literature and discuss both strengths and limitations of "the new standard."
Keywords: B cells; membranous nephropathy; rituximab; nephrotic syndrome